## Simple và best practice solution for x^4=16 equation. Kiểm tra how easy it is, & learn it for the future. Our solution is simple, và easy khổng lồ understand, so don`t hesitate lớn use it as a solution of your homework.

If it"s not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for x^4=16 equation:

Simplifyingx4 = 16Solvingx4 = 16Solving for variable "x".Move all terms containing x to lớn the left, all other terms khổng lồ the right.Simplifyingx4 = 16Reorder the terms:-16 + x4 = 16 + -16Combine lượt thích terms: 16 + -16 = 0-16 + x4 = 0Factor a difference between two squares.(4 + x2)(-4 + x2) = 0Factor a difference between two squares.(4 + x2)((2 + x)(-2 + x)) = 0Subproblem 1Set the factor "(4 + x2)" equal to lớn zero and attempt khổng lồ solve:Simplifying4 + x2 = 0Solving4 + x2 = 0Move all terms containing x lớn the left, all other terms to lớn the right.Add "-4" to lớn each side of the equation.4 + -4 + x2 = 0 + -4Combine like terms: 4 + -4 = 00 + x2 = 0 + -4x2 = 0 + -4Combine lượt thích terms: 0 + -4 = -4x2 = -4Simplifyingx2 = -4The solution to lớn this equation could not be determined.This subproblem is being ignored because a solution could not be determined.Subproblem 2Set the factor "(2 + x)" equal to lớn zero và attempt to solve:Simplifying2 + x = 0Solving2 + x = 0Move all terms containing x to the left, all other terms lớn the right.Add "-2" to lớn each side of the equation.2 + -2 + x = 0 + -2Combine like terms: 2 + -2 = 00 + x = 0 + -2x = 0 + -2Combine lượt thích terms: 0 + -2 = -2x = -2Simplifyingx = -2Subproblem 3Set the factor "(-2 + x)" equal lớn zero và attempt lớn solve:Simplifying-2 + x = 0Solving-2 + x = 0Move all terms containing x lớn the left, all other terms to lớn the right.Add "2" lớn each side of the equation.-2 + 2 + x = 0 + 2Combine like terms: -2 + 2 = 00 + x = 0 + 2x = 0 + 2Combine lượt thích terms: 0 + 2 = 2x = 2Simplifyingx = 2Solutionx = -2, 2

### See similar equations:

| 3x^2-14+22x=0 || 5x^2-17x+6=6x-3 || X^3-3x^2+20x=0 || 3x^3-21=0 || 6x^2=0 || x+12x^2=-35 || (6w^3+8w)-(-8w^3-2w+3)= || 2x^4=7x^2+15 || (7z^2+8z)-(-3z^2-7z+3)= || (8x^3+6x^2y^2+6xy^2)+(4x^3y^2-4x^2y^2-4xy^2)= || (5w^8-8w^4+6w^2+5)+(9w^6+3w^4-7w)= || 5xy+3y^2-13xy+9y^2-4= || x^6-6x^5+7x^6-2x^5+4= || (2x^3+7x)-(-6x^3-6x+9)=t || -3x^3+9x^2-4x-1= || x^3-5x^2+x= || (7af-6a^2f+16af^2)-(11af^2-3af-16a^2f)= || (2x^3+7x)-(-6x^3-6x+9)= || (8x^3y^2+5x^2y^2+5xy^2)+(4x^3y^2-3x^2y^2-3xy^2)= || (8t^8-6t+7t^2+2)+(2t^7+3t^4-5t)= || (8t-6t+7t^2+2)+(2t^7+3t^4-5t)= || 11ab+3b^2-4ab+3b^2-10= || x^5-6x^4+9x^5-4x^4+2= || 6x^2+3=0 || 6x^2-3=0 || 5x^5+4x+14=0 || 4p^2+68p+168=0 || 6k^2+84k+270=0 || 6k^2+84k=270 || 6a^2+48a-54=0 || 6x^2-19x=0 || 6x^2-19+14=0 |